A Digital Innovation-Based Creative Economy Model for MSMEs Growth: Theoretical Integration and Practical Insights from an Emerging Economy - Hastalona, Dina; Hasibuan, Eka Hayana; Lazuardi, Dedy (Theoretical and Practical Research in Economic Fields, 2026)
The acceleration of economic growth in the digital era requires a strategic transformation of the small and medium enterprises (SMEs) sector, particularly through the adoption of creative economy frameworks underpinned by digital innovation. This study investigates the influence of digital innovation integration on SME growth by employing a quantitative approach using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). A total of 250 SME actors in Medan City were selected through purposive sampling to participate in the study. The results indicate that digital literacy, digital infrastructure, stakeholder engagement, and creative collaboration exert a significant influence on digital innovation, which subsequently drives SME growth. Moreover, the Medan Go Creative model - comprising the dimensions of Go Digital, Go Global, and Go Green - emerges as an effective strategy for enhancing SME sustainability and competitiveness. The model demonstrates strong predictive relevance, with an R² value of 0.782 and a Q² value of 0.652. These findings contribute to the theoretical advancement of integrative models within the creative economy paradigm and provide practical insights for policymakers seeking to accelerate the digital transformation of SMEs at the local level.